Air-conditioning system : design manual - McKew, Howard J. (ASHRAE, 2019)
Offering real-world applications in addition to theoretical calculations and analytical procedures, the Third Edition, bridges the gap between theory and practice in the design of HVAC&R systems. It has been completely revised and updated to reflect current industry best practices.Organized into 13 chapters covering the design process, load calculations, systems components, and various types of HVAC&R systems, this manual is beneficial to both the entry-level designer and the experienced HVAC professional. New material on commissioning and testing, adjusting, and balancing (TAB); decentralized HVAC applications and central cooling and heating plants; and a designer's business plan has been added. In addition, significant updates and enhancements have been made to chapters on health, wellness, and safety; components; and special HVAC&R systems.
Keywords: Air conditioning.; elektronické knihy; electronic books